Variable morphology of the Madagascar endemic Aristida tenuissima (Poaceae: Aristidoideae) and the absence of Stipa (Poaceae: Pooideae, Stipeae) from Madagascar - Vorontsova, Maria S. (Phytotaxa, 2013)
The widespread and species rich grass genera Aristida Linnaeus (1753: 82; Aristidoideae) and Stipa Linnaeus (1753: 78; Stipeae) are ordinarily simple to distinguish by the characteristic three awns in Aristida and a single awn in Stipa. A study of Aristida in Madagascar shows that the Madagascar endemic Stipa perrieri A.Camus (1934: 593) is in fact a 1-awned variant of Aristida tenuissima Camus (1933: 844) described and illustrated by Bosser (1969). There are no collections of Stipa or other members of Stipeae recorded from Madagascar.